Meanings and Categories of Confusing Chinese Verbs “Gei (给)” “Jiao (叫)” “Qing (请)” “Rang (让)” “Shi (使)”: A Semantic Analysis - Soontornthamniti, Nititaya (Journal of Arts and Thai Studies, 2024)
Objectives: This article is a study on the meanings of five Confusing Chinese verbs, namely gei (给), jiao (叫), qing (请), rang (让), and shi (使), through the framework of semantics to analyze and identify similarities and differences among them. This analysis will contribute to a systematic understanding of the meaning of these Confusing Chinese verbs. Methods: The data for analysis include book, Chinese dictionary, and a collection of official examination papers of the Chinese proficiency test (HSK). This research analysis is through the framework of semantics and principled polysemy approach. Results: The result showed that all five Chinese verbs have both shared meanings and different meanings. Some meanings are commonly used daily, while others are more historical, idiomatic, or used in spoken language. Moreover, the perception of similar meanings among words may vary, indicating diverse perspectives. The confusing Chinese verbs can be categorized into four aspects based on shared meanings. These groups include verbs related to causing someone to do something, granting permission, causing results, and inviting. The meaning that is shared across all five Chinese verbs is “to cause someone to do something”. Additionally, there are different meanings and categories, divided into twelve aspects. These groups include giving things or experiences, human or animal voices, calling out, naming, requesting, buying religious statues, agreeing, granting rights, wishing, being inferior, avoiding, and using. Application of this study: It is shown that five verbs are verbs that have complex semantic relationships. Analyzing and understanding the multiple meanings and analyzing the semantic relationships of these verbs systematically can assist in their accurate usage.